Effect of CeO2 on High-Temperature Oxidation Performance of Electron Beam Cladding NiCoCrAlY Coating on Ni-Based Alloy. (14th April 2020) - Liu, Hailang; Huang, Yiping; Wang, Xiaoyu; Lu, Ruxue
Abstract : In order to enhance the high-temperature oxidation resistance properties of Inconel 617 alloy, NiCoCrAlY and NiCoCrAlY CeO2 composite powder coatings metallurgically bonded to substrate were prepared on the surface of Inconel 617 alloy by electron beam cladding. The effect of rare earth oxide CeO2 on the oxidation resistance of NiCoCrAlY coating was investigated. The isothermal oxidation behavior of the substrate and NiCoCrAlY cladding layer with different CeO2 contents (1%, 2%, 3%, and 4%) and without CeO2 oxidized at 1050°C for 20 h, 40 h, 60 h, and 100 h was analyzed. The microstructure and phase composition of the coating after electron beam treatment were tested. The results show that the self-repair of Al2 O3 and Cr2 O3 oxide film can be improved under a high-temperature oxidation environment with the addition of CeO2, and the oxidation resistance of NiCoCrAlY coating can be effectively strengthened by adding CeO2 . The improvement effect is most obvious when the content of CeO2 is 2%.